Legal Regulation of the Free Medicinal Aid in the Russian Federation - M. V. Podvyaznikova (Сибирское юридическое обозрение, 2013)
The problems of provision with medicinal aid the citizens of the Russian Federation for the out-patient treatment are analyzed in the article.